Acculturation of entrepreneurial activity: An exploratory case study of several mosques in Kelantan - Mohd Rushdan Yasoa; Mohd Safwan Ghazali; Mohd Afifie Mohd Alwi; Azira Hanani Ab. Rahman; Siti Salwani Abdullah; Ahmad Ridhuwan Abdullah; Mohammad Ismail; Mohd Rafi Yaacob (Medwell Journals, 2017)
The main purpose of this study is to identify the entrepreneurial activities run by mosques that were chosen based on their entrepreneurial attributes. This study was conducted using qualitative data selection through in depth interviews on three different mosques in Kelantan. The findings of this study show that their entrepreneurial and business activities were still at an average level. This was due to the fact that all of the mosques under study were strategically located and thus would not have any problems in regards to receiving continuous public contributions. However, there are ways suggested by the study to acculturate entrepreneurial activities in their management.